The sepulchral monument of Cardinal Cisnéros before and after the bombardment. Series of 2 photos. And the baptimal basin of Cervantes
The sepulchral monument of Cardinal Cisnéros before and after the bombardment. Series of 2 photos. And the baptimal basin of Cervantes.